Samuel Adams papers - Adams, Samuel, 1722-1803.
Nineteen volumes containing correspondence, speeches, petitions, committee records, and other papers relating chiefly to Adams's political life in Massachusetts. Correspondents include John Adams, John Burgoyne, Christopher Gadsden, Horatio Gates, Elbridge Gerry, Nathanael Greene, Thomas Jefferson, Arthur Lee, Richard Henry Lee, Thomas Paine, and James Warren.
Photostats of the originals in the New York Public Library.
New York Public Library
Continental congressman and governor of Massachusetts.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, John, -- 1735-1826 -- Correspondence; Burgoyne, John, -- 1722-1792 -- Correspondence; Gadsden, Christopher, -- 1724-1805 -- Correspondence; Gates, Horatio, -- 1728-1806 -- Correspondence; Gerry, Elbridge, -- 1744-1814 -- Correspondence; Greene, Nathanael, -- 1742-1786 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Lee, Arthur, -- 1740-1792 -- Correspondence; Lee, Richard Henry, -- 1732-1794 -- Correspondence; Paine, Thomas, -- 1737-1809 -- Correspondence; Warren, James, -- 1726-1808 -- Correspondence; Massachusetts -- Politics and government -- 18th century; Delegates, U.S. Continental Congress -- Massachusetts; Governors -- Massachusetts